Editor's Choice - Frailty and the management of patients with acute cardiovascular disease: A position paper from the Acute Cardiovascular Care Association. Issue 2 (1st March 2018) - Walker, D M; Gale, C P; Lip, G; Martin-Sanchez, F J; McIntyre, H F; Mueller, C; Price, S; Sanchis, J; Vidan, M T; Wilkinson, C; Zeymer, U; Bueno, H
Abstract: Frailty is increasingly seen among patients with acute cardiovascular disease. A combination of an ageing population, improved disease survival, treatable long-term conditions as well as a greater recognition of the syndrome has accelerated the prevalence of frailty in the modern world. Yet, this has not been matched by an expansion of research. National and international bodies have identified acute cardiovascular disease in the frail as a priority area for care and an entity that requires careful clinical decisions, but there remains a paucity of guidance on treatment efficacy and safety, and how to manage this complex group. This position paper from the Acute Cardiovascular Care Association presents the latest evidence about frailty and the management of frail patients with acute cardiovascular disease, and suggests avenues for future research.